Analisis Pengaruh Belanja Modal terhadap Aset Tetap dan Ekuitas Pemerintah Daerah di Provinsi Riau - Priyatmo, Tri; Rahayu, Winarni; Akbar, Rusdi (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
Nearly two decades since the Indonesian government’s financial reports began to be prepared in 2004, the government’s equity growth ratio has generally experienced a downward trend. This condition also occurs at the regional government level in Riau Province. Asset components, especially fixed assets, strongly influence government equity. Government fixed assets are formed from capital expenditures carried out every year. However, to date, the capital expenditure implemented by the government has not been able to encourage an increase in fixed assets and government equity. This research aims to measure the effect of capital expenditure on local government fixed assets. The analysis uses panel regression data consisting of cross-sectional data from eight districts/cities in Riau Province and time series data for 2015-2021. The data was processed using the E-Views 12 and SPSS 25 applications. The study results concluded that capital expenditure significantly positively influences fixed assets in local governments that have routine land capital expenditure every year. Every Rp. 1 increase in capital expenditure will affect an increase of Rp. 0.64 in local government fixed assets. In contrast, fixed assets are not significantly affected by capital expenditures in local governments, with irregular annual capital expenditures for land. These findings can enrich the literature and provide a new perspective for policymakers to increase government equity through land capital expenditure and improve the quality of fixed asset management, including evaluating fixed asset depreciation policies.